The Tradition of Mokhatamu Quru`ani for The Bride In The Marriage Customs (Study of Living Quran in Bongo Village, Batudaa Pantai District Gorontalo): Tradisi Mokhatamu Quru`ani Bagi Mempelai Wanita dalam Adat Pernikahan (Studi Living Quran di Desa Bongo kec. Batudaa Pantai Gorontalo) (Takwil: Journal of Quran and Hadith Studies, 2022)
This article discusses the practice of Mokhotamu Quru'ani for the bride in the Gorontalo Community Wedding Procession in Bongo Village, Batudaa Pantai District Gorontalo. The focus of this article is how the participants interpret the tradition reading of the Quran for the bride. To get the social meaning of this tradition, this research uses the Bronislaw Malinowski functionalism approach as a reference and data analysis. The results of this study concluded that Mokhotamu Quru'ani began since the acceptance of Islam as a religion and was integrated with local customs. The implementation of Mokhotamu Quru'ani is practiced with local culture which is based normatively through the philosophy of Adati Hula-Hulaa To Saraa, Saraa Hula-Hulaa to Quru'ani. In the practice the bride reads the Qur’an starts from Q.S. Ad-Duha to An-Nas and Ad-Dhuha. Mokhotamu Qurua'ni has a religious function as a guarantee of peace and happiness of marriage life. Based on the theory of functionalism, the tradition of Mokhotamu Quru'ani fulfil biological need, interumental needs and integrative needs.